New perspectives for mitotane treatment of adrenocortical carcinoma. Issue 3 (May 2020) - Puglisi, S.; Calabrese, A.; Basile, V.; Pia, A.; Reimondo, G.; Perotti, P.; Terzolo, M.
Abstract : Adrenocortical carcinoma (ACC) is an aggressive cancer characterized by poor survival. Apart from radical surgery, there is a limited range of therapeutic options and mitotane remains the cornerstone of medical treatment of ACC in either adjuvant or palliative settings. The aim of adjuvant mitotane therapy is to reduce the risk of ACC recurrence following surgical removal of the tumor. Use of mitotane in an adjuvant setting is off-label, but the recent guidelines endorsed by the European Society of Endocrinology (ESE) and the European Network for the Study of Adrenal Tumors (ENSAT) recommend it in ACC patients at high risk of recurrence. The palliative use of mitotane for treatment of advanced ACC aims at controlling tumor progression and, when present, hormone secretion. In this clinical setting, mitotane is used in association with chemotherapy to treat the more aggressive forms, while mitotane monotherapy is reserved for less progressive ACC. Many years after its introduction in clinical practice, there are still uncertainties surrounding the use of this old drug and the derived benefits. Moreover, physicians who use mitotane should recognize and manage the systemic effects of the drug that need a complex supporting therapy.